Shamanic Healing or Scientific Treatment?—Transformation of Khorchin Mongolian Bone-Setting in China - Meng, Gencang (Religions, 2023)
This paper, taking the medical practice of Khorchin Mongolian bone-setting as an example, examines the conflict and connection between religious healing and modern (or Western) medicine as well as the transformation of shamanisms in the discourse of nation-state building in China, and argues that the relationship between shamanic healing and modern medicine is not a binary opposition. Khorchin Mongolian bone-setting is the product of the interaction between alternative medicine and syncretistic local knowledge.